Effectiveness and safety of thread embedding acupuncture for facial nerve palsy sequelae: a protocol for a multicenter, assessor-blinded, randomized, controlled clinical trial - Kim, Jung-Hyun; Goo, Bonhyuk; Lee, Dongmin; Kim, Tae-Yoon; Park, Jun-Gyu; Kim, Eunseok; Nam, Sang-Soo (Frontiers in Neurology, 2025)
IntroductionFacial nerve palsy can result in various sequelae. Recent reviews and clinical studies reported that thread-embedding acupuncture is a safe treatment and can improve facial nerve palsy sequelae. This trial aims to confirm the effectiveness and safety of thread-embedding acupuncture for patients with facial nerve palsy sequelae.MethodsA multicenter, randomized, assessor-blinded clinical trial will be conducted. One hundred forty-two participants will be recruited by eligibility criteria and be randomly divided into two groups. The intervention group will receive thread-embedding acupuncture in addition to electroacupuncture, while the control group will be given only electroacupuncture. The primary outcome is a change in the physical function score of the Facial Disability Index. The secondary outcome is change in Sunnybrook Facial Grading System, Social/Wellbeing function score of Facial Disability Index, Synkinesis Assessment Questionnaire, Numeric Rating Scale of stiffness by facial region, Patient Global Impression of Change, Euro-Qol 5-Dimension 5-level, Economic evaluation questionnaire and adverse events. Assessment points include before treatment (Week 1), after treatment completion (Week 6), 2 weeks post-treatment completion (Week 8, Primary endpoint), and 10 weeks post-treatment completion (Week 16).ConclusionThis randomized controlled trial will assess the effectiveness and safety of thread-embedding acupuncture treatment alongside electroacupuncture for facial nerve palsy, using proper sample sizes and rigorous methodologies to address previous research limitations.Clinical trial registrationhttps://cris.nih.go.kr/cris/search/detailSearch.do?seq=25846&status=5&seq_group=24726&search_page=M, identifier KCT0008551.